The Representations of Traditional Culture And Ancient Chinese In The Movie "Chang'an Animation": 《长安动画》电影中传统文化与古代汉语的表征 - Achmad Marzuqi; Octi Rjeky Mardasari; Dudy Syafruddin (Journal of Chinese Language and Culture Studies, 2026)
This study aims to systematically analyze the representation of ancient Chinese culture and Classical Chinese in the animated film Chang’an, and to explore students’ comprehension of the film within a learning context. This research employs multiple data collection methods, including observation and documentation of dialogues, poetic lines, classical idioms, visual symbols, and the cultural contexts presented in the film; the distribution of questionnaires to ten students; and the application of triangulation to examine the validity and reliability of the findings. The results indicate that the differences between Classical Chinese and modern Chinese in Chang’an are primarily reflected in personal pronouns, polite expressions, expressions of friendship, leave-taking, and apologies. The Classical Chinese used in the film is characterized by syntactic ellipsis and structural compactness, frequently omitting subjects, objects, or predicates, while meaning can still be inferred from the context. In addition, the archaic elegance, parallelism, idiomatic features, and metaphorical expressions found in classical vocabulary enhance both the symbolic meaning and aesthetic value of the language, reflecting the traditional style of ancient Chinese language and literature. An analysis of character dialogues and visual narration further reveals that the distinctive cultural values of the Tang Dynasty are represented through aspects such as loyalty, hierarchical etiquette, poetic aesthetics, and traditional knowledge. Students’ responses also demonstrate that audiovisual media can enhance the understanding of Classical Chinese in a more contextualized, interactive, and meaningful manner. Therefore, Chang’an can be regarded as a pedagogically valuable medium that supports culture-based instruction in Classical Chinese.